(untitled) (Zaporizhzhia Historical Review, 2021)
ХІХ century is the period of reconciliation two ideologis-liberalism and social-democratism. E.Bernshtein accorded socialism to liberalism. Ideologists of liberalism called self socialists. Modern democracy without liberalism is a way to dictatorship.